FIRST LANGUAGE ACQUISITION, THE PROCESSES AND DEVELOPMENT - Sarwanti, Sri . (Majalah Transformatika, 2010)
This article attempts to find out the processes and development of first language Acquisition. The processes are started from the first day children are born. Because of the existence of a device called Language Acquisition Device (LAD) the children are able to undergo several stages before they eventually arrive to a position which enables them to master the first language. The stages are reflexive crying and vegetative sounds, cooing and laughter, vocal Play, reduplicated babbling, non-reduplicated babbling and expressive jargon. Keywords :first language, LAD, processes, first words, first meaning, fis phenomenon